Cloning and Characterization of Partial Chlorophyll a Oxygenase (CAO) Gene Involved in Soybean Shade Tolerance Mechanism - Khumaida, Nurul; Kisman, Kisman; Sopandie, Didy (Department of Agronomy and Horticulture, IPB University, 2015)
Plant tolerance mechanism under shade stress is indicated by high chlorophyll-b content, which is synthesized from chlorophyll a by chlorophyll a-oxygenase (CAO) gene. The study was aimed to clone and characterize the partial of CAO gene involved in shade tolerance mechanism in soybean. Total RNA was isolated from the second trifoliate leaves of soybean plants and the first strand cDNA was prepared using Reverse Transcriptase Moloney Murine Leukemia Virus (RT-M-MLV) (RNase H-). Northern blot hybridization was used to analyze expression of partial CAO gene. The result showed that one partial gene, CAO 3-4 (1,052 bp), comprised of 292 adenine (a), 241 cytosine (c), 276 guanine (g) and 242 thymine (t), therefore the number of amino acid deduction was 338. The expression of CAO 3-4 partial gene was higher in shade tolerant genotypes than in shade sensitive genotypes, both under 50% shade and dark. These results demonstrated that the CAO gene is involved in shade tolerance mechanism of soybean.